Leadership style in Swiss evangelical churches in the light of their historically shaped leadership culture - Russenberger, M. (Koers, 2010)
This article is a sociological-historical study of the inter-relation between the historically developed leadership culture of democracy and leadership practice in the evangelical churches of Switzerland. Contemporary Swiss leadership style is based on the cultural inheritance of the Celts, the Romans and the Germanic tribes, the foundation of the Confederation, as well as the history of Christianity. The core values that shaped Swiss leadership culture are the idea that not too much power should vest in the individual, that there should be a democratic right of co-determination, that there should be federal freedom, and that work and achievement are very important. These same basic values still affect leadership in Swiss evangelical congregations today.